Pengelolaan Sampah Dengan Pendekatan Partisipasi Masyarakat - Nimas Ajeng Sitoresmi; Mila Karmilah (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
The large percentage of waste is a problem and an opportunity in solving waste problems. Waste management is a systematic, comprehensive, and continuous activity that includes waste reduction and handling. What can be done is by involving and providing education to the community that produces waste. Community participation in waste management is basically interpreted as actively participating in a series of waste management, transportation, and disposal activities based on self-awareness and responsibility to achieve targets in creating a clean and healthy environment. The purpose of this paper is to describe waste management, stages of participation, types of participation, and levels of community participation in waste management in 3 case studies, namely the Margaluyu Environment, Bone Puteh Hamlet and Palattae Village.